PENGAWASAN STASIUN PENGISIAN BAHAN BAKAR UMUM OLEH DINAS PERINDUSTRIAN DAN PERDAGANGAN KOTA PEKANBARU TAHUN 2012 - Kurniawan "; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Research on the Control of Fuel Filling Station Public By the Department of Industry and Trade of the city of Pekanbaru in 2012. Research is done to determine and analyze the implementation of the monitoring stations that are Pekanbaru. The problem formulation is encapsulated in the formulation of the problem, namely the implementation of the Monitoring How General Fuel Filling Station by the Department of Industry and Trade of the city of Pekanbaru in 2012?, And Why Monitoring conducted by the Department of Industry and Trade of the city of Pekanbaru In 2012 less than optimal?In this study, the authors used a qualitative approach as a method of problem solving and discovery of data sources. The data required in this study is primary data is data directly from the informer research and research findings when the study was conducted. Research data collection techniques are interview techniques and engineering documentation. Furthermore, after the data obtained is analyzed with descriptive technique, which is done by analyzing the data and facts.The results showed that the implementation of the Department of Industry and Commerce oversight Pekanbaru City in 2012 is still not optimal, this is due to oversight conducted by the Department of Industry and Trade of the city of Pekanbaru is based on reports perkasus. Supervision of the Department of Trade and Industry conducted in Pekanbaru include first Supervision of Institutional / Legal Business, the second Supervision of Availability / Supply, a third of the Price Supervision, Supervision of fourth Purpose / Objective / Usage, fifth Monitoring of the Size / Gauge Pump. The factors that cause less than optimal surveillance conducted by the Department of Industry and Trade of the city of Pekanbaru is human resources are inadequate in monitoring both in terms of quantity and skill or ability. Facilities and infrastructure are also not sufficient in terms of oversight and budget to support the implementation of the gas station less supervision.Keywords: Monitoring, Disperindag, Gas Stations